Recall referendums in Peruvian municipalities: a political weapon for bad losers or an instrument of accountability?. Issue 7 (9th November 2016) - Welp, Yanina
ABSTRACT: Between 1997 and 2013, more than 5000 recall referendums were activated against democratically elected authorities from 747 Peruvian municipalities (45.5% of all municipalities). This makes Peru the world's most intensive user of this mechanism of direct democracy which is designed to remove elected authorities from office before the end of their term. What are the reasons for this extensive use of recall referendums in Peru and, more importantly, what consequences do they have in terms of democratic legitimacy and government efficiency? This paper sets out to answer these questions by comparing the Peruvian case against the background of other countries in the Andean region. It proposes an explanation for the intensive activation of recall procedures through the combination of two factors: first, the features of the institutional design of the mechanism, which affect the probability of a successful activation of recall referendums, and second, the degree of institutionalization of political parties, which influences the incentives of political actors to gain power between regular elections.